Localização automática de pontos de controle em imagens aéreas baseada em cenas terrestres verticais - Berveglieri, Adilson [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Control field is essential in image orientation procedures and is based on the determination of ground coordinates from distinguishable features. Aerial survey techniques have evolved with the integration of Global Navigation Satellite System (GNSS) and inertial systems, enabling Direct Sensor Orientation (DSO). However, even with the development and consolidation of these techniques, Ground Control Points (GCPs) are still needed to correct for systematic errors and to assess the reliability and accuracy of the orientation data. The location of GCPs over images is still a task performed by an operator, which is an additional source of errors due to the uncertainties in the visual identification. Thus, an automatic flow is proposed in this work to obtain GCP coordinates and locate them in aerial images with sub-pixel accuracy. The approach is based on vertical ground scenes from distinguishable feature areas with a point surveyed by GNSS receiver (like a GCP). These ground scenes are matched with aerial image patches to transfer surveyed points. Feature- and area-based matching algorithms are applied for this task as well as a subsequent adaptive refinement by least squares. To perform the automatic flow, a technique to acquire ground images as required was designed. In addition, other techniques were developed to: prepare control scenes by rectification and orthorectification; locate GCPs into search window in aerial images, and minimize the differences between matched image patches, improving the sub-pixel location of the match point. Different experiments assessed the feasibility and accuracy achieved with the proposed techniques using bundle adjustment in stereo-models and image blocks. The analysis of results was based on discrepancies and residuals at GPCs and independent checkpoints...

Os pontos de controle são fundamentais nos processos de orientação de imagens. Mesmo com o desenvolvimento e consolidação das técnicas de levantamento aéreo pela integração de Sistemas de Posicionamento por Satélites (Global Navigation Satellite System - GNSS) e sistema inercial, que possibilitam a orientação direta do sensor, pontos de controle são necessários para corrigir erros sistemáticos e avaliar a confiabilidade e a acurácia dos dados. A localização desses pontos de controle nas imagens ainda é uma tarefa realizada por um operador, sendo uma fonte adicional de erros devido às incertezas na identificação visual. Assim, este trabalho propõe um fluxo automático para obter coordenadas de pontos de controle e localizá-las nas imagens aéreas com precisão subpixel. A abordagem baseia-se em cenas terrestres verticais de áreas com características distinguíveis, contendo um ponto levantado por receptor GNSS (como um ponto de controle). Essas cenas terrestres são usadas na correspondência com janelas em imagens aéreas para transferir o ponto levantado. Algoritmos de correspondência de imagem baseada em área e em características são aplicados nessa tarefa, além de um posterior refinamento adaptativo por mínimos quadrados. Para realizar o fluxo automático, desenvolveu-se uma técnica de coleta de imagens terrestres na forma necessária. Além dessa técnica, outras foram desenvolvidas para: preparar a cena terrestre de controle com retificação e ortorretificação; localizar o ponto de controle em janela de busca na imagem aérea e minimizar as diferenças na correspondência entre imagens terrestre e aérea, definindo melhor a posição subpixel do ponto. Vários experimentos avaliaram a viabilidade e a acurácia alcançada com as técnicas propostas usando ajustamento por feixes de raios em modelos e blocos de imagens...
Keywords: Cartografia; Fotogrametria; Imagens digitais; Sistemas de navegação global por satélite; Cartography